Volcanic stratigraphy and evidence of magma mixing in the Quaternary Payún Matrú volcano, andean backarc in western Argentina - Hernando, Irene (2012)
Fil: Hernando, Irene. Centro de Investigaciones Geológicas (CONICET-UNLP); Argentina.